2023
DOI: 10.3390/ijms241411679
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs and Human Diseases: Current Status and Future Perspectives

Abstract: Non-coding RNAs (ncRNAs) are a family of RNA molecules that, unlike messenger RNAs, are not templates for protein synthesis but have an essential or regulatory role in this process [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recent evidence shows that non-coding RNAs (ncRNAs) play a fundamental role in various biological processes associated with the pathogenesis, risk stratification, prognosis prediction, and therapeutic strategy of EC patients. [44][45][46] Recent studies have reported the use of circulating micro RNAs as diagnostic biomarkers in EC. It has been reported that hundreds of ncRNAs are potentially deregulated in EC and ncRNAs can be detected in the blood circulation; therefore, circulating ncRNAs can be fast, accurate, and minimally invasive diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that non-coding RNAs (ncRNAs) play a fundamental role in various biological processes associated with the pathogenesis, risk stratification, prognosis prediction, and therapeutic strategy of EC patients. [44][45][46] Recent studies have reported the use of circulating micro RNAs as diagnostic biomarkers in EC. It has been reported that hundreds of ncRNAs are potentially deregulated in EC and ncRNAs can be detected in the blood circulation; therefore, circulating ncRNAs can be fast, accurate, and minimally invasive diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%
“…These features include the noncoding nature of both lncRNAs and circRNAs that allow them to actively involve in gene expression regulation (69,70), and stability in various body fluids making them readily accessible for noninvasive detection (71,72). Besides, these biomarkers are resistant to enzymatic degradation (73).…”
mentioning
confidence: 99%